Selected results of the hypersonic flight experiment STORT - Gülhan, Ali; Hargarten, Dorian Amadeus; Zurkaulen, Maximilian; Klingenberg, Florian; Siebe, Frank; Willems, Sebastian; Di Martino, Giuseppe; Reimer, Thomas (Acta Astronautica, 2023)
The three-stage rocket configuration of the hypersonic experiment STORT with several scientific payloads concerning hypersonic technologies was launched successfully from the Andøya Space launch site in northern Norway on 26th June 2022. The third stage performed a suppressed trajectory to increase integral heat load on the payload structures. The vehicle traveled at speeds above Mach 8 at altitudes between 30 km and 38 km for more than 60 seconds. The nose and forebody section of the payload was made of CMC structures. Three canards with a CMC thermal protection were equipped with thermal management experiments to verify the thermal efficiency of these methods. All engineering science experiments like aerothermal heating of the nose and forebody, CMC material response at temperatures above 2200 K, hypersonic thermal management, shock wave boundary layer interaction, CFRP module with cork coating for high temperature applications, high temperature fin leading edge and radiometer sensors provided unique flight data. A reduced in-flight 3 DoF trajectory simulation running on the flight computer determined the ignition time of the third stage which allowed improved experiment conditions in terms of Mach number and apogee altitude even in the presence of external perturbations